A Case Report on Ceftriaxone Induced Periorbital Edema - Mathew, Binu; Thomas, Sunitt; Kumar, Shiv; Hiremath, Doddaya; Doggalli, Rita (Journal of Pharmacy Practice and Community Medicine)
Ceftriaxone is a third generation cephalosporin antibiotic, used commonly due to their broad spectrum of activity. As the therapeutic use of cephalosporin are increasing, reports of hypersensitivity reactions are also on the rise. Allergic reactions to beta-lactamase antibiotics are the most common cause of adverse reactions mediated by specific immunological mechanism. A 25-year-old female Para 1, living 1 (P1, L1) with 39 weeks and 4 days of gestation was hospitalized in the Obstetrics and Gynecology department. On examination, contracted pelvis was present, so lower uterine segment caesarean section was done. A test dose of 0.1 ml of ceftriaxone was given intradermal pre-operative, which was non-reactive. Later, injection ceftriaxone 1 g IV was given, following which she developed periorbital edema after 20 min. Ceftriaxone was withdrawn. On examination, there was swelling and puffiness of eyelids and around the right eye. The patient was administered Inj. Avil 2 ml (Pheniramine Maleate) IV stat as treatment. Periorbital edema is a rare presentation of adverse drug reaction produced by ceftriaxone.
Keywords: Adverse drug reactions; Anaphylaxis; Ceftriaxone; Hypersensitivity reactions; Naranjo scale; Periorbital edema.